SYNTHESIS OF TELECHELIC POLYMERS OF 2-ETHYL-2-OXAZOLINE WITH VINYL AND QUATERNARY AMMONIUM FUNCTIONAL GROUPS - Carlos Rueda, Juan (2025)
New telechelic polymers (MKA-1 and MKA-2) of 2-ethyl-2-oxazoline (Etoxa) containing vinyl and quaternary ammonium terminal groups were synthesized. The synthesis was carried out by cationic ring-opening polymerization of Etoxa in acetonitrile at 75°C, initiated by para-chloromethylstyrene and terminated by N,N'-dimethyldodecylamine. The telechelic polymers were structurally characterized by nuclear magnetic resonance (1H-NMR and 13C-NMR) and by infra red spectrometry (FTIR). Quantitative analysis of the 1H-NMR spectra determined that the degrees of polymerization of the telechelic polymers MKA-1 and MKA-2 were 21,4 and 9,2 units, respectively. These values were in agreement with the initial molar ratio Etoxa/CMS for MKA-1 and MKA-2 (21,1 and 9,0, respectively). Likewise, 1H-NMR determined that the degrees of functionalization with quaternary ammonium groups of the telechelic MKA-1 and MKA-2 were 98 and 99%, respectively. The molecular weights of MKA-1 and MKA-2, obtained from the degrees of polymerization, were 2455 and 1243 g/mol, respectively.